2017
DOI: 10.1038/bjc.2017.230
|View full text |Cite
|
Sign up to set email alerts
|

TCTP as a therapeutic target in melanoma treatment

Abstract: Background:Translationally controlled tumour protein (TCTP) is an antiapoptotic protein highly conserved through phylogeny. Translationally controlled tumour protein overexpression was detected in several tumour types. Silencing TCTP was shown to induce tumour reversion. There is a reciprocal repression between TCTP and P53. Sertraline interacts with TCTP and decreases its cellular levels.Methods:We evaluate the role of TCTP in melanoma using sertraline and siRNA. Cell viability, migration, and clonogenicity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…For instance, it was reported that sertraline could induce ER calcium release in PC3 human prostate cancer cells ( 50 ). In addition, sertraline interacted with translationally controlled tumor protein and decreased its cellular levels, resulting in diminished migration properties and colony formation capacity of melanoma cells ( 51 ). Therefore, further experiments are needed to clarify whether these genes or pathways contributed to autophagy induction by sertraline.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was reported that sertraline could induce ER calcium release in PC3 human prostate cancer cells ( 50 ). In addition, sertraline interacted with translationally controlled tumor protein and decreased its cellular levels, resulting in diminished migration properties and colony formation capacity of melanoma cells ( 51 ). Therefore, further experiments are needed to clarify whether these genes or pathways contributed to autophagy induction by sertraline.…”
Section: Discussionmentioning
confidence: 99%
“…Sertraline is now being tested in phase I/II clinical studies [101]. Recently, it was demonstrated that TCTP is a promising target in melanoma, also using sertraline as a drug [102]. In our initial experiments targeting TCTP, we employed anti-histaminic drugs [79].…”
Section: Mechanisms Of Cancer Promotion By Tctpmentioning
confidence: 99%
“…Only scarce mixed preclinical data are available regarding a possible effect of AD on melanoma tumors. Whereas some studies suggested that certain ADs may be effective in inhibiting tumor growth in a murine model, have an in‐vitro cytotoxic activity against human melanoma cells or possess antioxidant activity in mice, other studies indicated that selective serotonin reuptake inhibitors may increase mice brain metastases or not affect them (Boia‐Ferreira et al, ; Herr, Mohile, van, Brown, & Rich, ). To the best of our knowledge, no clinical studies evaluated this question, which is particularly intriguing since melanocytes originate from the embryonic ectoderm, similarly to the central nervous system.…”
Section: Discussionmentioning
confidence: 99%